Cost-effectiveness of rivaroxaban versus enoxaparin for the prevention of postsurgical venous thromboembolism in Canada - Diamantopoulos, Alexander; Lees, Michael; Wells, Philip S.; Forster, Fiona; Ananthapavan, Jaithri; McDonald, Heather (Thrombosis and Haemostasis, 2010)
This study aimed to evaluate the cost-effectiveness of prophylaxis with rivaroxaban vs. enoxaparin in the prevention of venous thromboembolism (VTE) after total hip replacement (THR) and total knee replacement (TKR) from the perspective of the Canadian healthcare system. A model was developed that included both acute VTE (represented as a decision tree) and long-term complications (represented as a Markov process with one-year cycles). Transition probabilities were derived from phase III clinical trials comparing rivaroxaban with enoxaparin and published literature. Costs were derived from the Ontario Case Costing Initiative and publicly available sources. Utilities were derived from published literature. The model reported VTE event rates, quality-adjusted life expectancy and direct medical costs over a five-year horizon. Costs are reported in 2007 Canadian Dollars (C$). When rivaroxaban and enoxaparin are compared in patients undergoing THR, rivaroxaban dominates enoxaparin. That is, rivaroxaban is associated with improved health outcomes as measured by increased quality-adjusted life years (QALYs; 0.0006) and fewer symptomatic VTE events (0.0061), and also with lower cost (savings of C$300) per patient. Similarly, rivaroxaban dominates enoxaparin in patients undergoing TKR, achieving a gain of 0.0018 QALYs, a reduction of 0.0192 symptomatic venous thromboembolic events and savings of C$129 per patient. Rivaroxaban is a cost-effective alternative to enoxaparin for VTE prophylaxis in patients undergoing THR and TKR. Over a five-year horizon, rivaroxaban dominated enoxaparin in the prevention of VTE events in patients undergoing THR and TKR, providing more quality-of-life benefit at a lower cost.
Keywords: Anticoagulants; surgery; thrombosis